Beneath my mother's feet - Qamar, Amjed (New York Atheneum Books for Young Readers, 2008)
When her father is injured, fourteen-year-old Nazia is pulled away from school, her friends, and her preparations for an arranged marriage, to help her mother clean houses in a wealthy part of Karachi, Pakistan, where she finally rebels against the destiny that is planned for her.
Keywords: Family life -- Pakistan -- Fiction; Household employees -- Fiction; Self-actualization (Psychology) -- Fiction; Sex role -- Fiction; Poverty -- Fiction; Pakistan -- Fiction